The Association Between Hepatitis B Virus Mutations and the Risk of Liver Disease and Hepatocellular Carcinoma - Akrami, Hassan; Monjezi, Mohammad R.; Ilbeigi, Shahrzad; Amiri, Farshid; Fattahi, Mohammad Reza (Current Molecular Medicine, 2022)
Hepatitis B virus [HBV], the best-described hepadnavirus, is distributed all around the world and may lead to chronic and acute liver disease, cirrhosis, and hepatocellular carcinoma. Despite the advancement in treatment against HBV, an errorprone reverse transcriptase, which is required for HBV replication as well as host immune pressure, leads to constant evolution and emergence of genotypes, subgenotypes and mutant viruses; so, HBV will remain as a major healthcare problem around the world. This review article mainly focuses on the HBV mutations which correlated to occult HBV infection, immune escape, vaccine failure and eventually liver cirrhosis and HCC. The current study indicated that preS/S region mutations are related to vaccine failure, immune escape, occult HBV infection and the occurrence of HCC. Whereas P region Mutations may lead to drug resistance to NA antivirals. PreC/C region mutations are associated with HBeAg negativity, immune escape, and persistent hepatitis. Moreover, X region Mutations play an important role in HCC development.
Keywords: HbeAg